A Comparative Literature review of Educational Policy Strategies in Indonesia and Singapore Toward Global Quality Standards - Mariam, Timtim Siti; Darmawan, Deni; Omonovich, Khammataliev Dostnazar; Kibrio, Burieva (Jurnal Ilmiah Global Education, 2025)
This study aims to compare education policies implemented in Singapore and Indonesia, with a focus on their alignment with global standards for quality education. Using a literature review methodology, the study explores how government policies, educational equity, infrastructure development, and technology integration influence the educational frameworks in both countries. The study specifically highlights the implementation of policies and outcomes in each country. The analysis shows that Singapore’s education system is better organized, more effective, and more aligned with international best practices. This is largely due to significant investment in education reform, on going teacher development, and strong government support. On the other hand, Indonesia’s education system faces challenges such as uneven policy implementation, inadequate infrastructure, and significant gaps in the quality of education between urban and rural areas. Despite these challenges, Indonesia has made significant progress in improving access to education and promoting inclusiveness, especially in remote and less developed areas. This study provides important insights for policy makers seeking to improve education systems in their respective countries. By comparing policy implementation and outcomes, this study offers practical recommendations for advancing education programs in Indonesia, with an emphasis on equity and achieving higher international standards. The findings also emphasize the crucial role of government support and resource allocation in ensuring the success of education reforms.